Core-shell magnetic-plasmonic nanoparticles enclosed in biocompatible hydrogels for multimodal cancer therapy - Veloso, Sérgio Rafael Silva (2019)
In this work, superparamagnetic manganese ferrite nanoparticles, either coated with a gold shell or decorated with gold nanoparticles, were successfully incorporated into a new self-assembled peptide-derived hydrogel. The new magnetogels were tested as drug nanocarriers and photothermia capabilities were evaluated following the release of a model drug (curcumin).